Effects of Different Acetic Acid Immersion Time on the Properties of Collagen from Pangasius Skin - Clara Amelia Kusumawinahyu; Sharilla Aryananti Abidin; Patmawati; Dwi Yuli Pudjiastuti; Dwitha Nirmala; Mochammad Amin Alamsjah; Laksmi Sulmartiwi; Raseetha Vani Siva Manikam (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research